Platelets in myeloproliferative neoplasms have a distinct transcript signature in the presence of marrow fibrosis. (19th August 2019) - Guo, Belinda B.; Linden, Matthew D.; Fuller, Kathryn A.; Phillips, Michael; Mirzai, Bob; Wilson, Lynne; Chuah, Hun; Liang, James; Howman, Rebecca; Grove, Carolyn S.; Malherbe, Jacques A.; Leahy, Michael F.; et al.
Summary: Marrow fibrosis is a significant complication of myeloproliferative neoplasms (MPN) that affects up to 20% of patients and is associated with a poor prognosis. The pathological processes that lead to fibrotic progression are not well understood, but megakaryocytes have been implicated in the process. The aim of this study was to determine whether platelets, derived from megakaryocytes, have transcriptomic alterations associated with fibrosis. Platelets from MPN patients with and without fibrosis and non‐malignant control individuals were assessed using next generation sequencing. Results from the initial training cohort showed discrete changes in platelet transcripts in the presence of marrow fibrosis. We identified more than 1000 differentially expressed transcripts from which a putative 3‐gene fibrotic platelet signature ( CCND1, H2AX [previously termed H2AFX ] and CEP55 ) could be identified. This fibrosis‐associated signature was assessed blinded on platelets from an independent test MPN patient cohort. The 3‐gene signature was able to discriminate between patients with and without marrow fibrosis with a positive predictive value of 71% (93% specificity, 71% sensitivity). This demonstrates that assessment of dysregulated transcripts in platelets may be a useful monitoring tool in MPN to identify progression to marrow fibrosis. Further, sequential monitoring could have clinical applications for early prediction of progression to fibrosis.